MANAGING WORK STRESS THROUGH COPING MECHANISM - Lathifah Nur Azizah (Insains Institute, 2023)
The purpose of this research is to determine the effect of job stress on employee performance with coping strategies as a moderating variable. The population in this study were employees of regional-owned bank. The number of respondents taken in this study were 40 respondents. Based on the results of research using SPSS shows that job stress and coping strategy have a significant effect on employee performance. Coping strategies moderate the effect of work stress on employee performance. The implication of the above is that in an effort to pay attention to work stress in employees because work stress can reduce employee performance. Ways that should be used to increase work stress, namely the company by giving appreciation or reward to employees of regional-owned bank and interaction with co-workers and good superiors so that the more satisfied employees are with their work, the more it will trigger employees to perform better. The more satisfied employees will be with their work, it will trigger employees to work even harder and of course it will have an impact on improving company performance.